Acoustic damping flexible polyurethane foams: Effect of isocyanate index and water content on the soundproofing. Issue 15 (20th December 2018) - Baghban, Sahar Abdollahi; Khorasani, Manouchehr; Sadeghi, Gity Mir Mohamad
ABSTRACT: High‐efficiency sound absorbing flexible polyurethane foams (FPUFs) are manufactured using nonpolar polyester resin, methylene diphenyl diisocyanate, and other reagents by one‐shot bulk polymerization. In this study, the impact of the isocyanate index (90, 100, and 110) and water content (2.5 and 5%) on the microphase separation and soundproofing behavior of FPUFs are examined using atomic force microscopy, Fourier transform infrared spectroscopy, optical microscope, and an impedance tube device. The results reveal that the increase of the isocyanate index and water content leads to the increase of the cell size, cell size distribution, open‐cell content, cell wall roughness, and microphase separation. Also, maximum sound absorption coefficient (α) reaches to 0.98 and the average of α in the frequency range of 1500–4000 Hz increases from 0.7 to 0.87 by increasing the water content from 2.5 to 5% and isocyanate index from 90 to 110; therefore, acoustic damping performance enhances up to 26.24% due to the synergic effects of microphase separation on the viscose media formation, open‐cell content, cell wall roughness, cell size, and cell size distribution. In conclusion, FPUFs with an optimal amount of microphase separation and drainage flow can be a promising candidate for sound insulating materials. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47363. Abstract :